Improvement of whole wheat dough fermentation for steamed bread making using selected phytate-degrading Wickerhamomyces anomalus P4. (July 2021) - Li, Zhijian; Zhou, Mengmeng; Cui, Mingyu; Wang, Yuanhui; Li, Haifeng
Abstract: Whole wheat steamed bread is highly recommended because of its health benefits. However, the presence of phytate negatively influences dough properties, because it binds minerals and proteins. In this study, a yeast strain with phytate-degrading activity, namely, Wickerhamomyces anomalus P4 was isolated from whole wheat dough fermented with Jiaozi. The yeast's ability to degrade phytate during whole wheat dough fermentation and its suitability for steamed bread making process were evaluated. W. anomalus P4 showed strong phytate degradation ability, and more than 45% of the initial phytate was degraded after 12 h of whole wheat dough fermentation. Degradation of phytate by W. anomalus P4 was fast in the first 4 h and then slowed gradually with time. The use of the selected W. anomalus P4 as a starter improved dough microstructure and increased mineral solubilization in comparison with commercial Saccharomyces cerevisiae . W . anomalus P4 fermented steamed bread had higher lightness and height/diameter ratio, and similar protein digestibility as the steamed bread prepared by commercial S. cerevisiae . Therefore, phytate-degrading W. anomalus strain P4 could potentially provide benefits by decreasing the phytate content in whole wheat dough for steamed bread making. Graphical abstract: Image 1 Highlights: Wickerhamomyces anomalus P4 with high phytate-degrading activity was isolated. Degradation of phytate by W. anomalus P4 was fast in the first 4 h of fermentation. W. anomalus P4 improved dough microstructure and increased mineral solubilization.